A multicenter study of thromboembolic events among patients diagnosed with ROS1-rearranged non-small cell lung cancer. (April 2020) - Alexander, Marliese; Pavlakis, Nick; John, Thomas; O'Connell, Rachel; Kao, Steven; Hughes, Brett G.M.; Lee, Adrian; Hayes, Sarah A.; Howell, Viive M.; Clarke, Stephen J.; Millward, Michael; Burbury, Kate; et al.
Highlights: ROS1 rearranged NSCLC confers thrombotic risk. Incidence of pulmonary embolism, concurrent and recurrent thromboembolism is high. Thromboembolism occurs beyond the peri-diagnostic period. Thromboembolism occurs irrespective of therapeutic strategy. Abstract: Objectives: This study aimed to describe the longitudinal thromboembolism (TE) risk relative to the natural history of disease and clinical course of ROS1 rearranged non-small cell lung cancer (NSCLC). Materials and Methods: Cases of ROS1 -rearranged NSCLC from six Australian hospitals were pooled and evaluated for incidence, timing, predictors and outcomes of venous or arterial TE, as well as objective response rate (ORR) to active therapy and overall survival (OS). Results: Of 42 patients recruited, 20 (48%) experienced TE; one (2%) arterial, 13 (31%) a pulmonary emboli (PE), and 12 (29%) a deep vein thrombosis. Among those with TE, six (30%) experienced multiple events, three as concurrent and three as recurrent diagnoses. The cumulative incidence of TE over time, adjusted for death as a competing risk factor, approached 50%. TE occurred prior to, during and post the peri-diagnostic period and occurred irrespective of treatment strategy. A thrombophilia was identified in n = 3/10 (30%) cases screened: in two factor V Leiden and in one anti-thrombin III (ATIII) deficiency. Median OS was 21.3 months in those with TE vs. 28.8 months in those without; hazard ratio 1.16 (95%CI 0.43–3.15). Respective ORR to first-line therapy with TE was 50% vs. 44% without TE in the chemotherapy arm and 67% vs. 50% in the targeted therapy arm. Conclusion: In the rare cancer subtype, ROS1, these real-world data demonstrate sustained TE risk beyond the diagnostic period irrespective of therapeutic strategy. High incidence of PE, concurrent TE, and recurrent TE warrant validation in larger cohorts. Consideration of primary thromboprophylaxis in ROS1 populations is recommended.